2020
DOI: 10.1007/s10877-020-00558-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the PSI response in general anesthesia

Abstract: In anesthesia automation, one of the main important issues is the availability of a reliable measurement of the depth of consciousness level (hypnosis) of the patient. According to this value, the hypnotic drug dosage can be adequately calculated. One of the most studied hypnosis indexes is the bispectral index (BIS). In this article we analyzed an alternative called patient state index (PSI). The objectives of this study are, first, to validate the accuracy of the PSI describing the hypnosis level during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In previous publications [ 24 , 28 , 29 ], an inhibitory sigmoidal model was used to describe the relationship between PSI and propofol dose in humans. However, other investigations performed under inhalant anaesthesia found that the dose-effect relationship of EEG-derived variables obtained from BIS and Narcotrend devices was better described with the combination of two fractional sigmoid E max models [ 26 , 27 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous publications [ 24 , 28 , 29 ], an inhibitory sigmoidal model was used to describe the relationship between PSI and propofol dose in humans. However, other investigations performed under inhalant anaesthesia found that the dose-effect relationship of EEG-derived variables obtained from BIS and Narcotrend devices was better described with the combination of two fractional sigmoid E max models [ 26 , 27 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can collect information from both sides of the brain to detect asymmetry in the patient's electrical activity. Next, this algorithm is improved by considering individual background differences and brain responses of different patients to different anesthetics [12,31]. Finally, less impact of the shock device on the PSI value during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography (EEG) is considered to be an important part of monitoring organs in anesthesia management [11]. The patient state index (PSI, SedLine® Root, Masimo Inc., Irvine, CA, USA) [12] is a reference index provided by the SedLine Brain Monitor, with a reference range of 0-100 and an ideal anesthetic depth of 25-50 (compared to 40-60 recommended by other monitors). It has been shown to be similar to the change of the bispectral index (BIS, Medtronic, Minneapolis, Minnesota, USA) during induction, maintenance and wake-up [13,14].…”
Section: Introductionmentioning
confidence: 99%
“… 8 21 30 33) It is important to carefully monitor and titrate the depth of sedation by medical professional with expertise in TBI management, as over-sedation can result in negative outcomes such as prolonged cognitive dysfunction, hemodynamic instability, and ventilator-associated pneumonia. 36 37 41 49) Bispectral index (BIS) and patient state index (PSI) based on electroencephalogram are the most widely used devices for measuring sedation depth. 2) As neurological examination can be challenging in patients with TBI undergoing deep sedation, it is crucial to utilize monitoring devices like pupilometer or intracranial pressure (ICP) measurement to supplement the assessment of neurological function.…”
Section: Introductionmentioning
confidence: 99%